ANALISIS DETERMINAN STATUS GIZI PADA REMAJA SEBAGAI LANGKAH MENDUKUNG PROGRAM NASIONAL MBG - Nilam Noorma; Yunita Kholilaili Saras Wati; Kamrianti Ramli; Fitriani Rahmatismi Blongkod (Ensiklopedia Research and Community Service Review, 2026)
Abstract: Adolescence is a very important period in the human life cycle because it marks the transition from childhood to adulthood. Based on the results of a preliminary study conducted at a high school in Semarang on 30 adolescents measured using the Body Mass Index (BMI), the results showed that 16.7% of adolescents were undernourished, 50% had normal nutritional status, and 33.3% were overweight. The objective of this study was to analyze the determinants of nutritional status among adolescents as a step toward supporting the national MBG program. A cross-sectional study design was used. The study was conducted at a high school in Semarang City in May 2026. The sample consisted of 80 respondents. Stratified random sampling was used. A research questionnaire served as the data collection instrument. Data analysis was performed using univariate and bivariate methods. The results showed an association between family income (p-value: 0.042) and nutritional knowledge (p-value: 0.030) and the adolescents’ nutritional status. It is recommended that community health centers and schools launch nutrition-related programs for students to improve their knowledge and awareness of nutrition so that they can apply it in their daily lives.Keywords: Nutrition Knowledge, Family Income, Adolescents.